"Noises off--" [videorecording (DVD)] - Burnett, Carol; Caine, Michael; Hagerty, Julie; Henner, Marilu; Linn-Baker, Mark; Reeve, Christopher, 1952-2004; Ritter, John, 1948-2003; Sheridan, Nicolette, 1963-; Frayn, Michael
A travelling theater group has so much going on behind the curtain, they almost ruin their performance in front of the curtain.